Occupational exposure to benzene in China. - Yin, S N (1987)
Of a total of 528,729 workers exposed to benzene or benzene mixtures in China, 508,818 (96.23%) were examined. Altogether 2,676 cases of benzene poisoning were found, a prevalence of 0.15%. A higher prevalence of benzene poisoning was found in the cities of Hangjou, Hefei, Nanjing, Shenyang, and Xian. The geometric mean concentration of benzene in 50,255 workplaces was 18.1 mg/m3 but 64.6% of the workplaces had less than 40 mg/m3. There was a positive correlation between the prevalence of benzene poisoning and the concentration in shoemaking factories. The prevalence of benzene induced aplastic anaemia in shoemakers was about 5.8 times that occurring in the general population. The results of this investigation show the need for a practicable hygiene standard to prevent benzene poisoning.